Calidad en la docencia del área económico-administrativa del ITSA - Onchi Hernández, Corina (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
The educational quality is at the moment a constant preoccupation of all Institution of Superior Education and their effects in the learning of the students cannot be misestimated. The participation of the professors for the profit of the quality is substantial, for that reason, in this investigation it is tried to present as it is same according to the educational perspective and the pupils of the administrative economic area of the ITSA. Educational of quality is that worries about its constant improvement that it first of all looks for to carry out his profession in such a way that it can create in the students enthusiasm in the knowledge, is to say to offer a service of quality. Within this investigation one exposes the application of a survey and its results, destined the professors and pupils of an institution of superior education, the Superior Technological Institute of Apatzingán, in his economic-administrative area; it looks for an approach the reality of the educational ones of this institution, that put under the analysis, reflection and critic, allows to identify the present profile of its professors and to detect the lines to follow in a program of continuous formation. The investigation turns around three concrete objectives: a) the validation of the questionnaire applied to the educational ones that it will allow to collect about his work within teaching. b) The identification of the educational performance of the economic-administrative area of the ITSA, from the obtaining of the results thrown by the answers given by the students of the Lic. In accountant’s office of the questionnaire. c) The detection of necessities of continuous formation an lines of formation of the university teaching staff of the economic-administrative academy.

La calidad docente es actualmente una preocupación constante de toda Institución de Educación Superior y sus efectos en el aprendizaje de los alumnos no pueden ser desestimados. La participación de los profesores para el logro de la calidad es sustancial, por ello, en esta investigación se pretende dar a conocer como se encuentra la misma de acuerdo a la perspectiva docente y alumnado del área económico administrativa del ITSA. Un docente de calidad es aquel que se preocupa por su mejora constante, que busca ante todo desempeñar su profesión de tal manera que pueda crear en los alumnos entusiasmo en el conocimiento, es decir brindar un servicio de calidad. Dentro de esta investigación se expone la aplicación de una encuesta y sus resultados, destinada a los profesores y al alumnado de una institución de educación superior, el Instituto Tecnológico Superior de Apatzingán en su área económico-administrativa; busca un acercamiento a la realidad de los docentes de dicha institución, que sometido al análisis, reflexión y crítica, permita identificar el perfil actual de sus profesores y detectar las líneas a seguir en un programa de formación continua. La investigación gira en torno a tres objetivos concretos: a) La validación del cuestionario aplicado a los docentes que permitirá recoger la información acerca de su trabajo dentro de la docencia. b) La identificación del desempeño docente del área económico-administrativa del ITSA, a partir de la obtención de los resultados arrojados por las respuestas dadas por los alumnos de la Licenciatura en Contaduría de los cuestionarios. c) La detección de necesidades de formación continua y líneas de formación del profesorado universitario de la academia económico-administrativa.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2006-0029; Educación; Superior; IES; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5820